Frequency of Nail Abnormalities in Children and Adolescents Admitted to a Dermatology Outpatient Clinic - Atiye Akbayrak; Tuba Kasap; Zennure Takçı; Havva Yıldız Seçkin (Galenos Yayinevi, 2021)
Aim:The incidence and spectrum of nail abnormalities in children differ from adults. The aim of this study is to investigate the frequency and spectrum of nail abnormalities in children and adolescents admitted to a dermatology outpatient clinic.Materials and Methods:This cross-sectional study included 600 patients under the age of 18 who presented at a dermatology outpatient clinic with various dermatological complaints between March and May 2018.Results:In this study, among 600 patients; 325 (54.16%) were female and 275 (45.84%) were male. The mean age was 9.18±5.12 years (1 month to 17 years). Nail abnormalities were present in 226 patients of whom 131 (58%) were female and 95 (42%) were male. The rate of nail abnormalities was 37.66% (226/600) among the study group. The number of nail abnormalities detected was 288 and the number of abnormality types was 23. The most common group of nail abnormalities were surface (18.16%) and colour (16.50%) changes. The most common nail abnormalities were leukonychia (16.50%), onychoschizia (6.5%), and onychophagia/onychotillomania (6.5%). Fingernail abnormalities were significantly higher in males than females. Leukonychia and onychophagia/onychotillomania were significantly higher in males than females. The rate of patients observed with ungual complaints among the patients with nail abnormalities was 10.61% (24/226).Conclusion:Nail abnormalities are very common in childhood. Although patients do not have a primary complaint, evaluation of the nails during physical examination may prevent the occurrence of permanent damage to the nails and stop the spread of infectious diseases to other nails.